1992
DOI: 10.1159/000098996
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Stimulation for Seizure Control: 17-Year Study

Abstract: Since 1974, 32 seizure patients have undergone chronic cerebellar stimulation (CCS); 27 have been contacted with 9 (7 spastic, 2 epileptic) continuing to use CCS for an average of 14.3 years (10–17 years). 6 (67%) are seizure-free and 3 (33%) have a reduction of seizure frequency. In the last 2 years, 2 other patients with spastic seizures, who were using CCS for 13 years, died of respiratory illness; 1 had been seizure-free and the other had a reduction. Of the remaining 16 patients (12 spastic, 4 epileptic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 0 publications
3
74
1
2
Order By: Relevance
“…The reason for this difference may be the rigorous methods by which we measured cerebellar volumes and defied CA. After normalization for total brain volume, the prevalence of CA in our patients decreased to 16.2%. This finding suggests that in as many as a third of patients, with apparent CA, a proportionate degree of generalized cerebral atrophy is also present.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The reason for this difference may be the rigorous methods by which we measured cerebellar volumes and defied CA. After normalization for total brain volume, the prevalence of CA in our patients decreased to 16.2%. This finding suggests that in as many as a third of patients, with apparent CA, a proportionate degree of generalized cerebral atrophy is also present.…”
Section: Discussionmentioning
confidence: 53%
“…the cerebellar volumes, CA was present in 25.9% of the epilepsy patients; with normalization, it was present in only 16.2%. The atrophy was symmetric between the cerebellar hemispheres, and there was no significant difference in volume between the hemisphere ipsilateral and the hemisphere contralateral to the side of the temporal lobectomy.…”
mentioning
confidence: 90%
“…demonstrated that 23 of 32 patients (85%) benefited overall from long-term CS. 66 Controlled, double-blind trials, however, demonstrated improvement in only 2 of 14 patients (14%). 67,68 A recent double-blind trial of 5 patients demonstrated a significant reduction in generalized tonic-clonic seizures and tonic seizures at 2 years follow-up.…”
Section: Cerebellummentioning
confidence: 98%
“…One patient, whose epilepsy failed to respond to stimulation, died as a result of a seizure 17 months after electrode implantation. Davis and Emmonds 16 subsequently discovered that 23 of 27 evaluable patients who underwent long-term CS (average follow-up 14.3 years) had an overall reduction in seizure frequency. Interestingly, 12 of the patients had a nonfunctioning stimulator at the time of the report, yet 5 were found to be seizure-free, and 7 had experienced a reduction in seizure frequency.…”
Section: Cerebellar Stimulationmentioning
confidence: 99%